ANFIS-Controlled High Step Up DC DC Converter for Fuel Cell Systems with Enhanced Efficiency Against Load Variation - Harmini Harmini; Mochamad Ashari; Feby Agung Pamuji (Universitas Muhammadiyah Malang, 2026)
The primary challenge in utilizing Fuel Cell (FC) systems lies in their inherently low and fluctuating output voltage, which contrasts with the requirements of a Direct Current (DC) bus network that demands a stable and relatively high voltage level. Ensuring consistent voltage regulation in the DC bus network is essential for reliable system performance. An interface converter is required to elevate and stabilize the voltage output under dynamic operating conditions. This paper introduces a high step-up DC–DC converter integrated with an Adaptive Neuro-Fuzzy Inference System (ANFIS)-based control scheme for enhancing the performance of FC power systems. The proposed work encompasses the modeling, analytical design, and structural development of the converter and its intelligent control mechanism. The proposed high step-up converter exhibits a novel structural configuration that integrates a clamp unit, a Multiplier Cell (MC), and cascaded Quadratic Boost Converter (QBC) stages. The contribution of this converter topology lies in its ability to enhance the reliability of fuel cell–based renewable energy systems, achieve high voltage amplification, ensure optimal efficiency, and maintain dynamic stability. This topology is specifically developed to attain an ultra-high voltage conversion ratio, achieving a significant voltage gain of up to 9.65 times, thereby effectively increasing the input voltage from 45 V to 400 V. The ANFIS controller effectively maintains a stable output voltage of 400 V with a maximum deviation of only ±3.5%. The proposed converter achieves a peak efficiency of 87% under varying load conditions, demonstrating its suitability for fuel cell-based energy systems.